Levantamento radiométrico em propriedades particulares localizadas na APA do rio Passaúna - Zamboni, Rodrigo Sanas (2024)
Naturally occurring radioactive materials have been present in several compartments of the ecosystem since the planet’s formation. Among them, in the decay series of primordial nuclides, radon isotopes stand out, which are responsible for more than half of the dose received by humans from natural radiation sources. Additionally, radon progeny are the second leading global cause of lung cancer, second only to tobacco. Besides radon, another significant isotope contributing to human exposure is 40K, which is widely disseminated in the Earth’s crust within specific sedimentary coverings. Consequently, monitoring active nuclides in rocks, soils, groundwater, and air in living environments is of paramount importance, both to provide data to the scientific community and to enable mitigative interventions for stakeholders. Therefore, the objective of this study was to conduct a radiometric survey in private properties located in the Rio Passaúna Environmental Protection Area (Curitiba, PR). For measuring concentrations of 222Rn and 226Ra in well water and 222Rn and 220Rn in soil air, the AlphaGUARD PQ2000 PRO (Saphymo, currently Bertin Technologies) was used. External surface gamma spectrometry was performed using the BRD-AT6101C portable scintillator (Atomtex). Gamma spectrometric data analysis detected the presence of 40K in all studied terrains, a finding consistent with the geological map of the state of Paraná, which indicates regions potentially rich in potassium feldspar. Other nuclides, such as 226Ra and 232Th, were also found on a smaller scale. Equivalent doses were relatively low, except for one point in one of the properties with an estimated dose value of 1.65 μSv/h. At this point, soil air measurement indicated a concentration of (664 ± 36) kBq/m3 of the isotope 220Rn. Regarding water, 7 out of 9 analyzed wells showed effective committed dose values for ingestion and inhalation of 226Ra and 222Rn above international reference levels, rendering these waters unsuitable for consumption from a radiological perspective. On the other hand, monitoring the air in residences showed values ranging from (30 ± 2) to (270 ± 20) Bq/m3, within normal limits. This work aligns with the federal concern regarding the basic radioprotection requirements in Brazilian territory, as established by the NN 3.01 standard of the CNEN, published in March 2024. It also has immediate social relevance and needs to be expanded in the region, where water supply is predominantly provided by wells. Furthermore, data of this nature are still incipient in the southern region of the country and require scientific attention.